Effects of gender grouping on students' group performance, individual achievements and attitudes in computer-supported collaborative learning. (July 2015) - Zhan, Zehui; Fong, Patrick S.W.; Mei, Hu; Liang, Ting
Highlights: 2M2F and 4F grouping are recommended; 1M3F grouping should be avoided. Males perform better in mix-gender groups; females perform equally in either group. Males prefer mix-gender, gender-balanced, and gender-majority grouping. Female students prefer single-gender grouping and gender-minority grouping. Gender differences mainly exist on attitude rather than learning achievement. Abstract: The purpose of this study was to examine the effects of gender grouping on students' group performance, individual learning achievements and attitudes in computer-supported collaborative learning (CSCL). 588 undergraduate students enrolled in a digital design course were randomly divided into 147 four-student groups that fell into five categories according to the composition of group members' gender, namely 4M (four males), 3M1F (three males and one female), 2M2F (two males and two females), 1M3F (one male and three females) and 4F (four females). Results indicated that: (1) For group performance, 2M2F and 4F groups significantly outperformed the other groups. (2) For individual learning achievements, no significant difference was found in females among different gender grouping interventions; however, males in mixed-gender groups performed significantly better than those in single-gender groups. (3) In terms of individual attitudes, males preferred mixed-gender, gender-balanced, and gender-majority grouping; however, females preferred single-gender and gender-minority grouping. (4) The effect of gender grouping mainly influences students' attitudes, rather than performance. These findings provide evidence that female-only and balanced-gender grouping are two kinds of good grouping interventions that could be recommended for CSCL, and male-minority groups should be avoided because they led to the worst group performance and individual attitudes.